"The oldest one in Russia" : the formation of the historiographical image of Valaam Monastery - Parppei, Kati (Russian history and culture, 2011)
Contributing, for instance, to the fields of nationality and borderland studies, this book offers a fascinating study of the process of "writing a worthy past" for the Russian Orthodox monastery of Valaam during the 18th and 19th centuries.